The tea shop on Lavender Lane - Roberts, Sheila, 1951- (Roberts, Sheila. 1951- Life in Icicle Falls., 2014)
Former caterer to the stars Bailey Sterling escapes to Icicle Falls after her business is detroyed by scandal, but the future of the tea shop she starts with her sister Cecily is threatened when they both fall for the same man.